Can metal-free silicon-doped hexagonal boron nitride nanosheets and nanotubes exhibit activity toward CO oxidation?. Issue 2 (18th November 2014) - Lin, Sen; Ye, Xinxin; Huang, Jing
Abstract : Si-doped hexagonal boron nitride nanosheets and nanotubes have been investigated by first-principle methods. Abstract : Si-doped hexagonal boron nitride nanosheets (Si-BNNS) and nanotubes (Si-BNNT) have been investigated by first-principle methods. The strong interaction between the silicon atom and the hexagonal boron nitride nanosheet or nanotube with a boron vacancy indicates that such nanocomposites should be very stable. The significant charge transfer from the Si–BNNS substrate to the O2 molecule, which could occupy the antibonding 2π* orbitals of O2, results in the activation of the adsorbed O2 . The catalytic activity of the Si–BNNS for CO oxidation is explored and the calculated barrier (0.29 eV) of the reaction CO + O2 → CO2 + O is much lower than those on the traditional noble metals. This opens a new avenue to fabricate low cost and high activity boron nitride-based metal-free catalysts.